Studi Literatur Perbandingan Bahasa Pemrograman C++ dan Bahasa Pemrograman Python pada Algoritma Pemrograman - Adawiyah Ritonga; Yahfizham Yahfizham (Jurnal Teknik Informatika dan Teknologi Informasi, 2023)
Programming Language is a language used to write computer program codes. Programming languages ​​allow programmers to instruct computers to perform certain tasks. There are many different programming languages ​​such as Python, Java, C++, PHP, JavaScript and so on. This article only focuses on explaining the C++ and Python programming languages. The aim of this article is to find out the differences between the C++ and Python programming languages ​​and to find out the advantages and functions of each programming language. From the results obtained, the two C++ programming languages ​​are more focused on Windows development, while Python is more often used in software development and the C++ programming language is more difficult to understand than the Python programming language.